The entomopathogenic fungus, Metarhizium anisopliae for the European grapevine moth, Lobesia botrana Den. & Schiff. (Lepidoptera: Tortricidae) and its effect to the phytopathogenic fungus, Botrytis cinerea - Aguilera Sammaritano, Juan Alberto (2018)
The European grapevine moth, Lobesia botrana Den. & Schiff. (Lepidoptera: Tortricidae) and the gray rot fungus (Botrytis cinerea) are two important factors that cause elevated losses of productivity in vineyards globally. The European grapevine moth is one of the most important pests in vineyards around the world, not only because of its direct damage to crops, but also due to its association with the gray rot fungus; both organisms are highly detrimental to the same crop. Currently, there is no effective, economic, and eco-friendly technique that can be applied for the control of both agents. On the other hand, Metarhizium anisopliae belongs to a diverse group of entomopathogenic fungi of asexual reproduction and global distribution. Several Metarhizium isolates have been discovered causing large epizootics to over 300 insects’ species worldwide. In this study, a simple design was conducted to evaluate the potential of native M. anisopliae isolates as one of biological control agents against L. botrana and as possible growth inhibitors to B. cinerea. Entomopathogenic fungal strains were isolated from arid soils under vine (Vitis vinifera) culture. Results suggest that the three entomopathogenic strains (CEP413, CEP589, and CEP591) were highly efficient in controlling larval and pupal stages of L. botrana, with mortality rates ranging from 81 to 98% (within 4–6 days). Also, growth inhibition over B. cinerea strains resulted in percentages ranged from 47 to 64%. Finally, the compatibility of the entomopathogenic strains, with seven commercial fungicides, was evaluated. The potential of the entomopathogenic fungal strains to act as control agents is discussed.